Analisis Usability pada Aplikasi Siakad Gofeeder STP Reinha Larantuka Menggunakan Metode User Experience - Deta, Bernadete; Nobertus Pati Sekosi, Nobertus Pati (Jurnal Kridatama Sains dan Teknologi, 2024)
This research aims to determine the level of user satisfaction and findings of Gofeeder using the User Experience (UX) method, as well as providing recommendations for improving the system based on the research results. There are several aspects studied in this research, namely effectiveness, efficiency and user satisfaction using Gofeeder at the Renha Larantuka Pastoral College, reviewed by student users. Usability testing aims to determine whether an application meets user needs or not (User Experience). In this research, Usability testing was carried out at the Renha Larantuka Pastoral College using the interview method. The interview method was carried out to measure User Experience so that users' opinions about Gofeeder can be known. At this stage the researcher measured the level of usability using 3 aspects, namely the effectiveness aspect, the efficiency aspect, and the user satisfaction aspect by distributing a Google Form questionnaire to 82 respondents to determine the level of satisfaction with the web information system at Civitas STP Reinha Larantuka. The results of the usability measurements have an overall percentage score of 84.16%, in the table the feasibility category is in the interval 80 to 100, so it can be concluded that the results of the usability measurements on the STP Reinha Larantuka Website have a value of "Very Useful".